2010
DOI: 10.1007/s11064-010-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and β-adrenergic Receptors Inhibit Retinal Endothelial Cell Apoptosis Through Independent Pathways

Abstract: Diabetic retinopathy results from altered insulin receptor signaling. Based on previous studies demonstrating an interaction between β-adrenergic receptors and insulin signaling in hyperglycemic conditions, we hypothesized that β-adrenergic receptor stimulation and insulin stimulation would act synergistically to inhibit one of the hallmarks of diabetic retinopathy, namely retinal endothelial cell apoptosis. To test this hypothesis, human retinal endothelial cells were grown in high glucose (25 mM) medium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…After the appropriate treatment, cells were collected into lysis buffer and processed for Western blotting as we have done in the past [32,33]. Briefly, following cell lysis, protein concentrations are obtained using the Bradford assay.…”
Section: Methodsmentioning
confidence: 99%
“…After the appropriate treatment, cells were collected into lysis buffer and processed for Western blotting as we have done in the past [32,33]. Briefly, following cell lysis, protein concentrations are obtained using the Bradford assay.…”
Section: Methodsmentioning
confidence: 99%
“…The common GPCR, beta-adrenergic receptors have been previously shown to lose signaling capabilities with the onset of diabetes in various tissues throughout the body including the eye. 28,29,92,96,122 -adrenergic receptor as the dominant receptor subtype in regulation of insulin receptor signaling in retinal Müller cells.…”
Section: Discussionmentioning
confidence: 99%
“…39,59,103,122,[125][126][127] At a 2007 summer meeting of the Association for Research in Vision and Ophthalmology, it was suggested that diabetic retinopathy be defined as "structural and functional changes in the retina due to diabetes." The hyperglycemic environment caused by diabetes produces a number of vascular and neuronal changes in the retina, making the disease very difficult to describe and develop treatments.…”
Section: Chapter 5 General Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data support this finding that insulin receptor phosphorylation is significant reduced in retinal lysates from untreated diabetic rats. Insulin has been reported to be a survival factor for R28 cells (a retinal ganglion cell line) (Xiaochua et al 2004), as well as retinal endothelial cells (Panjala & Steinle 2011). The anti apoptotic actions of insulin occur through activation of Akt (Reiter et al 2006).…”
Section: Discussionmentioning
confidence: 99%